Colonic Adenocarcinoma with Plasmacytoid Feature: Histopathology and Molecular Characteristics of a Rare Neoplasm with an Unusual Presentation - Noor Marji; Jasrerman Dhillon; Gregory Y. Lauwers; Sebastian Feuerlein; Reza Nikfar; Monica Chatwal; Aram Vosoughi (Case Reports in Pathology)
Colorectal carcinoma with noncohesive tumor cells has been described in tumors with signet ring cells (mucinous adenocarcinoma and signet ring cell adenocarcinoma) and rhabdoid feature (carcinoma with sarcomatoid component). Cases of carcinoma with plasmacytoid morphology are rare in the gastrointestinal tract, and a single case of plasmacytoid colorectal carcinoma has been reported. We report the case of a 37-year-old woman who presented with urinary symptoms, hematuria, and abdominal pain. Imaging studies showed segmental sigmoid wall thickening with pericolic infiltration and focal bladder wall thickening. The cystoscopy with transurethral resection of bladder tumor revealed muscle invasion, dis-cohesive carcinoma with plasmacytoid morphology, which was initially misdiagnosed as the plasmacytoid urothelial carcinoma. Immunohistochemical stains showed the tumor cells to be positive for CDX2, CK20, and SATB2 and negative for p63, GATA3, CK7, and Uroplakin II, indicating the colorectal origin of the tumor. The subsequent colonic wall biopsy showed the same tumor. Molecular studies identified BRAF V600E, SMAD4, and p53 mutations associated with aggressive colorectal adenocarcinoma with mucinous/signet ring cell features. Further whole-exome sequencing and whole transcriptome analysis confirmed the colorectal origin of the tumor. This rare colorectal adenocarcinoma with the plasmacytoid feature may represent the signet ring cell adenocarcinoma lacking extracellular mucin or intracellular vacuole. Diagnosis of this rare histological subtype of colorectal carcinoma is important, particularly in the unusual presentation of this aggressive tumor.